Dari lapangan ke laporan: Narasi etnografi kegiatan KKN memaknai hari kemerdekaan di Desa Buntu Barana - Wahyu; Muhammad Yusril Samad; Edwin Sudirman; Dirga Rahmat; Arman Maulana; Agussalim; Suherman (P3HKI - Universitas Muhammadiyah Parepare, 2022)
A recurring challenge in implementing the Community Service Program (KKN) lies in students’ limited ability to understand the socio-cultural dynamics of local communities. As a result, activities often become technical and disconnected from the actual needs and values of the people. This study seeks to address that challenge by applying a participatory ethnographic approach to document and reflect on the involvement of Universitas Muhammadiyah Parepare students in community activities in Buntu Barana Village, Bungin Subdistrict, Enrekang Regency, particularly during the celebration of Indonesia’s 76th Independence Day. The students did not merely serve as facilitators but became active community members, engaging in planning, implementation, and evaluation processes. Through this engagement, it was revealed that the Independence Day celebration in the village was not just a symbolic event, but a platform for expressing solidarity, preserving the value of cooperation (gotong royong), and strengthening collective identity. The resulting ethnographic narrative illustrates a transformative learning experience for the students in understanding village life and national values from a grassroots perspective. This study highlights the importance of integrating ethnographic approaches in KKN to enable students to make more contextual, reflective, and meaningful contributions to community service practices.